Fruit peel as heterogeneous catalyst for biodiesel production - Mohamed Sharikh, Atikah; Sulaiman, Sarina; Azmi, Azlin Suhaida; Sulaiman, Siti Zubaidah (2017)
Scarcity in fuel from fossil fuel has led to exploration of potential substitutes from renewable sources. Identified as clear renewable energy to replace current fuel, biodiesel has been acknowledged to be more environmentally friendly in comparison to diesel from petroleum. This paper reports on the study of potassium carbonate, K2CO3 sourced from fruit peel as heterogeneous catalyst for biodiesel production. K2CO3 was produced by drying of fruit peel prior to calcination at temperature ranged from 700°C to 1000°C for 2 to 4 hours. To determine the physicochemical properties of the resulting ash, Fourier transform infrared (FTIR) and Scanning electron microscopy (SEM) analysis were employed for the characterization of the solid. Through FTIR analysis, the presence of carbonate was confirmed while SEM analysis revealed the morphological properties of the catalyst. This catalyst (2.7%) successfully enhanced the conversion of palm oil to biodiesel with highest yield of 94.4% at 60°C in the presence of 12:1 molar ratio of methanol to oil.